Menganalisis Pengelolaan Kelas pada Era Modernisasi di MA As-Sholchah - Nafisa, Mirzah; Rusniati, Rusniati; Luthfiah, Atiqotul; Fadilah, Solehatul (Jurnal Likhitaprajna, 2023)
This research focuses on: 1) How is classroom management in the modernization era? 2) How to manage a class where there are many students who commit juvenile delinquency? 3) What factors occur in juvenile delinquency? With research objectives: 1) To find out classroom management in the modernization era. 2) To find out the management of classes where there are many students who commit juvenile delinquency. 3) To find out what factors occur in juvenile delinquency. This study uses a qualitative approach to the type of research case study research (case study) and is descriptive. The source of the data in this research is the classrooms at MA As-Sholchah Warungdowo for the 2022-2023 academic year. This study used two data collection techniques, namely observation (observation) and teacher interviews. Based on the results of the study, it can be concluded that based on observations and teacher interviews, that class X IPS 2 students at MA As-Sholchah Warungdowo have many students who commit juvenile delinquency. The most dominant factor is external factors (school environment).